THE COMPARATIVE ELEMENT IN COMPARATIVE LEGAL LINGUISTICS - Galdia, Marcus (Comparative Legilinguistics, 2020)
Fundamental legal-linguistic research includes next to monolingual approaches to the legal language also comparative approaches. Meanwhile, the epistemic value of comparative approaches is unclear in legal linguistics. Therefore, in this article different legal-linguistic comparative approaches will be scrutinized, and their perspectives made operational in legal linguistics. Especially, the traditional analysis of legal terminology gains momentum here in the context of discursive comparative approaches. The multilingual origins and the intertextual mode of existence and development of the legal language clarify its specifics. They also shape processes in which the language of the global law emerges in the contemporary social reality.